Endoscopic curettage and bone grafting of the enchondroma of the proximal phalanx of the great toe. Issue 2 (June 2015) - Lui, T.H.
Highlights Enchondroma most often can be adequately treated with intralesional curettage and bone grafting. The portals should be as coaxial as possible during endoscopic curettage and bone grafting of the endochondroma. Complete curettage is assured during endoscopic procedure. Preservation of the periosteum during the endoscopic procedure is favorable for the bone regeneration and remodeling.